Froth flotation : a century of innovation - Fuerstenau, Maurice C.; Jameson, Graeme J.; Yoon, Roe-Hoan (Society for Mining, Metallurgy, and Exploration, 2007)
Froth Flotation: A Century of Innovation comprehensively describes the state-of-the-art research and practice in mineral froth flotation as known and practiced a century after its introduction. Recognized experts from around the world provide in-depth coverage on the historical aspects of flotation; flotation fundamentals; flotation chemistry; flotation cells, modeling, and simulation; and flotation plant practice.This commemorative volume is an invaluable reference for industry professionals, researchers, and graduate students. It continues a distinguished series that began with Froth Flotati.